A study of taxonomy of Salicornia L. in Ireland - Ferguson, I. K. (Ian Keith) (Trinity College (Dublin, Ireland), 1964)
Introduction: The genus Salicornia is a notoriously difficult group. The number and nature of the taxa recognised, especially within the annual section of the genus, has varied considerably according to the differing conceptions as to what constitutes a species in this group. There have been two main approaches to the taxonomy. The first was that adopted by many early workers which has been to regard all annual plants as belonging to one very variable species and this treatment has been used by many subsequent botanists who have had little acquaintance of the genus in the field. In the other approach there has been a tendency for the outlook to become more and more critical and the number of species described over the years is considerable. This variable treatment of the genus may be attributed to a number of reasons. The first is because the vegetative and floral parts of Salicornia are very reduced and specialised and as a result it is not possible to use many of those characters which are usually of value for the discrimination of taxa in other genera, A second reason for the difficult nature of the taxonomy of the group is that the characters used for the recognition of species show very few correlated discontinuities and in general variation is continuous. One of the main reasons for this continuous variation appears to be the extreme plasticity of the plants in response to environmental factors. Furthermore, there is a tendency for many plants to be cleistogamous, or if chasmogamous for self pollination to occur frequently and this type of breeding behaviour leads to the production of pure lines. The specialised habitat requirements namely a freedom from competition and a moist, saline soil, occur in a discontinuous manner along the coast in north west Europe. Discontinuous distribution acts as an isolating mechanism which prevents inter-colony gene exchange and thus contributes to the taxonomic difficulties of the group by causing local population or colony differentiation.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin 1964